Chronic Kidney Disease and Cognitive Dysfunction after Cardiac Surgery - Junping Du; Dou Dou; Rup Narayan Shah; Fuxia Yan; Zhiyan Han (Cardiovascular Innovations and Applications)
Patients with chronic kidney disease (CKD) often encounter cardiovascular complications, most commonly coronary heart disease. Although coronary artery bypass grafting is an effective treatment for this condition, many patients experience cognitive dysfunction after cardiac surgery. The complex interactions among functional status, general anesthesia, cardiopulmonary bypass, and surgical trauma in patients with CKD elevate the risk of neurological issues and increase the mortality rates after surgery. Consequently, both quality of life and overall prognosis are significantly affected. By reviewing recent research on postoperative cognitive dysfunction in patients with CKD, we sought to clarify the underlying mechanisms affecting this population and gain theoretical insights to help decrease perioperative CKD occurrence.